Sage-modified polydimethylsiloxane applied as antibacterial wound dressing material - Sara Sarraj; Małgorzata Szymiczek; Dariusz Jędrejek; Agata Soluch; Roksana Kurpanik (Polimery)
Materials based on polydimethylsiloxane have been developed with antibacterial activity and mechanical properties required for wound treatment. Sage herb (raw, modified, and polyphenol extract) was used as afiller in an amount of 5 and 10% by weight. Physicochemical, mechanical, and biological properties were examined. The results indicate abeneficial effect of sage modification on the tested properties.